Numerical simulation of the aluminum–zinc–steel galvanic system for new designs of automotive chassis. Issue 3 (30th August 2019) - Ruiz‐Garcia, Allan; Mayen‐Mondragon, Rodrigo; Genesca, Joan; Morales‐Murillo, Esteban; Taha‐Tijerina, Jaime; Montoya, Rodrigo
Abstract: The requirement for lighter vehicles in the automotive industry promotes designs based on the combination of different metallic alloys. Such an approach, however, leads to galvanic‐corrosion risks, which compromise the durability of vehicles. One proposal to minimize such risks is to separate some of the chassis components by a Zn washer. The present work uses the finite element method to evaluate such an innovative design. The capacity of the washer to protect its aluminum alloy and carbon steel neighbors is assessed. As a worst‐case scenario, the bare metals are in contact with NaCl solution. Two electrolyte layer thicknesses are assumed: in the micrometer and in the millimeter range. Each case requires different mathematical models. For the thin film case, the zinc washer is able to protect its neighbors from corrosion. However, it sustains large corrosion rates, and thus its protection is effective only during short periods. Furthermore, as the Zn surface degrades and thus recesses, the "protective field" is blocked by the neighboring metal‐walls. The thicker the electrolyte layer, the weaker the Zn protective capability and, at some point, the corrosion of the aluminum alloy is unavoidable. Abstract : The capacity of a zinc washer to protect its aluminum alloy and carbon steel neighbors is studied. The bare metals are under a sodium chloride solution. Thin and thick electrolyte films are assumed. For the thin film case, the washer protects its metallic neighbors from corrosion. However, the material corrodes fast. The thicker the electrolyte layer, the smaller the protection.